Increasing The Efficiency Of Plate Heat Exchanger (PHE) Economizer And Cooler Towards The Reduction Of Sterol Glucoside Components As Total Contaminants In Biodiesel - Boy Andika Sinaga; Dian Syahputra Saragi; Mangatur Febri V Pane; Frandika Darma (Institute of Advanced Knowledge and Science, 2025)
Sterol Glucoside is a total contaminant component in biodiesel products that can cause problems in biodiesel-fueled engines. Sterol glucoside will cause blockage in the fuel injection so that the distribution of fuel in the combustion chamber is uneven which has an impact on decreasing engine performance. The reduction of sterol glucoside in biodiesel products can be done by a filtration process at a lower temperature because the solubility of sterol glucoside in biodiesel decreases at lower temperatures. This study was conducted at a biodiesel production company located in Duri-Riau with a processing capacity of 25,000 kg/hour with the main raw material RBDPO. The process of reducing sterol glucoside as a total biodiesel contaminant predominantly occurs in the Biodiesel Drying Section where in this section there are equipment such as dryers, plate heat exchangers in the form of heaters, economizers, coolers and filtration. This study considers reducing the temperature of the final biodiesel product by adding plates to the economizer or cooler so that there will be an even better increase in heat transfer efficiency. The results obtained were the addition of 24 plates to the economizer with an increase in heat transfer efficiency of 6.6% and the final product output temperature of 32oC. The addition of 32 plate coolers resulted in an efficiency of 16.3% and a final product temperature of 35oC. The choice of adding plates to the economizer was made because it was more efficient in terms of cost and energy. The results of the analysis showed that the amount of sterol glucoside before the addition of the economizer plate was 18 ppm and after the addition of the economizer plate was 6 ppm or decreased by 66.7%.